Fully solution-processed InSnO/HfGdOX thin-film transistor for light-stimulated artificial synapse. (1st March 2022) - Li, Jun; Wen, Shengkai; Jiang, Dongliang; Li, Linkang; Zhang, Jianhua
Abstract: In recent years, the research interest in brain-inspired light-stimulated artificial synaptic electronic devices has greatly increased, due to their great potential in constructing low-power, high-efficiency, and high-speed neuromorphic computing systems. However, in the field of electronic synaptic device simulation, the development of three-terminal synaptic transistors with low manufacturing cost and excellent memory function still faces huge challenges. Here, a fully solution-processed InSnO/HfGdO X thin film transistor (TFT) is fabricated by a simple and convenient solution process to verify the feasibility of light-stimulated artificial synapses. This experiment investigated the electrical and synaptic properties of the device under light stimulation conditions. The device successfully achieved some important synaptic properties, such as paired-pulse facilitation, excitatory postsynaptic current and the transition from short-term memory to long-term memory. In addition, the device also exhibits brain-like memory and learning behaviors under different colors of light stimulation. This work provides an important strategy for the realization of light-stimulated artificial synapses and may have good applications in the field of artificial neuromorphic computing by light signals in the future.